Proximal hypospadias and 46XY disorder of sex development; which patient with hypospadias needs to be investigated? - Bayramoglu, Elvan; Bas, Veysel Nijat; Aycan, Zehra (Annals of Medical Research, 2021)
Aim: This study examines the distribution of genital abnormalities based on physical examination of our patients with 46, XY disorders of sex development (46, XY DSD), and aims to define severity and frequency of hypospadias in 46, XY DSD. Hypospadias is a relatively prevalent congenital anomaly. Although genetic, environmental and hormonal factors are considered to be responsible, etiology is not clarified in several hypospadias cases. Materials and Methods: Clinical, laboratory and genetic records of all cases with 46, XY DSD, who were evaluated by the sex determination monitoring board were retrospectively reviewed. In the diagnosis, hypospadias cases were examined in terms of the place of hypospadias and coexisting other external genital findings. Results: There were 72 patients with 46, XY DSD. 5-α reductase deficiency [n=32 (44.4%)] was the most commonly encountered diagnosis followed by androgen insensitivity syndrome [n=26, (36.1%)]. Proximal hypospadias were presented in 44.4% (n: 32) of the cases and only 6 of them (18.8%) were isolated hypospadias. In 81.2% of these cases, at least one of the anomalies such as cordi, bifid scrotum, undescended testis and micropenis accompanied proximal hypospadias. None of the distal hypospadias cases were referral clinic finding. Conclusions: 46 XY DSD is a heterogeneous group of patients with a varying age of presentation and a diverse clinical profile. It can be stated that proximal hypospadias is the most common referral clinic finding of 46, XY DSD, and the risk of 46, XY DSD increases with the intensifying degree of hypospadias and the presence of coexisting genital abnormalities such as cordi, bifid scrotum, undescended testis and micropenis.